Sustainability Reporting Practices in the Energy Sector of Bangladesh - Raquiba, Hasinat; Ishak, Zuaini (International Journal of Energy Economics and Policy, 2019)
Energy is a key component of production. In order to promote economic growth in a country, adequate supply of energy is pivotal. On the other hand, this sector is considered sensitive in terms of environmental and social sustainability. This article aims to depict the extent of sustainability-related reporting practices in 19 companies operating in the energy sector of Bangladesh through analyzing data from 2011 to 2017 from their annual reports. Besides, a few factors affecting the level of such disclosure have been considered using regression model. Legitimacy theory has been discussed as underpinning theory and some other previous studies have been consulted. Findings show that the level of sustainability related reporting practices in the sector is dismal, though positively influenced by ownership structure, media visibility, and characteristics of directors of the company. Policy implications are discussed. Keywords: Sustainability Reporting, Energy, GRI. JEL Classifications: G34, M48. DOI: https://doi.org/10.32479/ijeep.8621